Tunnel Magnetoresistance in Self-Assemblies of Exchange-Coupled Core/Shell Nanoparticles - Fabris, Fernando (2019)
We report the precise control of tunneling magnetoresistance (TMR) in devices of self-assembled core-shell Fe3O4/Co1-xZnxFe2O4 nanoparticles (0≤x≤1). Adjusting the magnetic anisotropy through the content of Co2+ in the shell, provides an accurate tool to control the switching field between the bistable states of the TMR. In this way, different combinations of soft-hard and hard-soft core/shell configurations can be envisaged for optimizing devices with the required magnetotransport response.